HUBUNGAN TINGKAT KECEMASAN DAN DEPRESI PADA PENGOBATAN TUBERCULOSIS (TBC) - Wijaya, Bagod Asturyno; Prasetyo, Joko; Santoso, Shelfi Retnani Putri (Universitas Pesantren Tinggi Darul Ulum, 2021)
AbstractTuberculosis is a major problem for Indonesia, where treatment requires a long time and must be regular for 6 to 8 months which can cause psychological problems such as anxiety, stress to depression.The research wants to explore through literature studies on the relationship between stress and depression in TB clients who are undergoing treatment as a basis for medical personnel to take action, in addition to treatment measures, psychosocial measures as management of TB can be effective. This review uses five databases in search (pubmed, Doaj, Sage, Wiley and google scholar) with published limits of 2015-2020 while the keywords used are medication, tuberculosis, anxiety and depression (Time to Treadment, Pulmonary Tuberculosis, Anxiety Scale and Depressive Disorder). The PRISMA diagram is used to shorten the selection of articles. There were 10,649 articles found, we found 10 articles that matched the inclusion criteria. Treatment with anxiety level, depression on TB treatment. In (n = 10) journals obtained, nine journals said there was a relationship between anxiety levels and depression levels on TB treatment, but one journal said there was no relationship between treatment and anxiety. And influenced by other factors.Keyword: anxiety, depression, tuberculosis treatment.